PHYSIOLOGY OF SOCCER IN THE HEAT - Gaung Perwira Yustika (Universitas Muhammadiyah Kudus, 2018)
Soccer is a sport play-able in various condition of environment, and one factor that affects this game is in heat situation, that can be one of key factor that change the match outcome. For the example is the big possibility that visiting team outside Arab countries gone to played at Gulf Region decreased winning possibility 3% for a increased 1°C temperature compared to the home team that easier to win under this circumstances. The home team had already aclimatized with the environment condition and often played in the heat temperature.Played soccer in the heat could increased sweat rate and peripheral vasodilation as a result to released the extra heat from the body, which affected dehidration phase and more metabolism to make more energy. In the elite level, pressure from the enviromental factors attracted the attention of both practitioners and the policy’s holders. In the Uni European Zone, match was usually played in the heat (example: at Madrid, Spain, at 30 degree of celcius). Temperature that exceeds 30 degree of celcius (maximum at 35 degree) for the example at the previous world cup 2014 Brazil could made the players got stressed because of the heat and got problems, one of them is decreased 3% of passing accuracy.